From civil society’s privatization and depoliticization to the centrality of the political praxis: on the difference and opposition between public-political and private in liberal political theories and institutionalized and universalist religions - Danner, Leno Francisco; Bavaresco, Agemir; Danner, Fernando (Aufklärung: journal of philosophy, 2018)
This paper criticizes (a) the separation between public-political versus private and unpolitical performed by liberal political theories, which constructs a very unclear and depoliticized sphere, subjects, values and practices that cannot be accessed neither by political-juridical institutions nor by social movements, citizen initiatives and political-cultural minorities, undermining a direct, participative and inclusive democratic political praxis as the basis of social criticism, cultural resistance and political emancipation by the very emphasis on the unpoliticity and privatization of civil society, its subjects, practices, values and clashes; (b) the political fundamentalism of institutionalized and universalist religions, which imposes the unpolitical private on the social, political, cultural and institutional sphere, from the delegitimation, silencing and marginalization of the differences, of the political praxis as a social struggle between opposed and different voices. We will propose that the possible way and strategy for a critical social theory and an emancipatory and inclusive democratic political praxis in face of this consolidated depoliticization of the praxis, civil society and institutions is to deconstruct such a separation between public-political and private by the politicization of civil society, its subjects, struggles, values and practices, which means that the foundation and application of a political theory into the social depends on the affirmation of the centrality of civil society’s political subjects and social clashes. Here, the praxis as politicity, carnality and permanent-pungent struggle and, as a consequence, the centrality of nowadays social-political subjects become the core of the theoretical-practical grounding and in terms of its link with the social sphere, subjects and clashes.